Analysing large one-day commodity futures price changes. (1st January 2014) - Hua, Wei; Wei, Peihwang
This paper analyses large one-day price changes in 26 US commodity futures, and it represents the first such attempt in commodity futures to our knowledge. Our results in general indicate a greater tendency for large changes to occur at the open, in commodity production months, and near futures maturity. We interpret these results as a consequence of information arrival. Subsequent to large price changes, we find a tendency for reversal, but the magnitude of reversal is not strong and can be explained by the market factor.